2015
DOI: 10.3233/jad-142763
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Discourse Complexity Preceding Alzheimer's Disease Diagnosis: A Case Study Comparing the Press Conferences of Presidents Ronald Reagan and George Herbert Walker Bush

Abstract: Changes in some lexical features of language have been associated with the onset and progression of Alzheimer's disease. Here we describe a method to extract key features from discourse transcripts, which we evaluated on non-scripted news conferences from President Ronald Reagan, who was diagnosed with Alzheimer's disease in 1994, and President George Herbert Walker Bush, who has no known diagnosis of Alzheimer's disease. Key word counts previously associated with cognitive decline in Alzheimer's disease were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 18 publications
5
75
0
Order By: Relevance
“…Our results suggested that the pMCI group expressed fewer semantic units and fewer unique words than the cognitively healthy group, which is a similar finding to that seen in studies with persons with MCI and AD [20, 21, 27, 28]. Recently, Berisha [28] found that former President Ronald Reagan's use of unique words declined over time, prior to his diagnosis of Alzheimer's Disease.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our results suggested that the pMCI group expressed fewer semantic units and fewer unique words than the cognitively healthy group, which is a similar finding to that seen in studies with persons with MCI and AD [20, 21, 27, 28]. Recently, Berisha [28] found that former President Ronald Reagan's use of unique words declined over time, prior to his diagnosis of Alzheimer's Disease.…”
Section: Discussionsupporting
confidence: 86%
“…Language measures were chosen based on previous literature that focused on discourse analysis in MCI or preclinical AD [18-20, 27, 28]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar pattern is found in AD; a comparison of the language production of Ronald Reagan – later diagnosed with AD – and George H.W. Bush – aging normally – uncovered that Reagan used words lower in imageabilty and used more indefinite nouns (e.g., anything, someone; Berisha et al, 2015). Patients with AD and individuals with hippocampal amnesia have similarities in their memory impairment and in MTL pathology.…”
Section: Introductionmentioning
confidence: 64%
“…Garrard, Maloney, Hodges, and Patterson (2005) found a longitudinal decline in the ratio of unique words to total word output in the writings of a renowned author who was subsequently diagnosed with AD. Similarly, Berisha, Wang, LaCross, and Liss (2015) documented a reduction in the number of unique words over time, along with an increase in conversational fillers and non-specific nouns in speeches delivered by President Reagan. Other studies have recorded an increase in the use of pronouns in language samples of individuals with AD (e.g., Ahmed, Haigh, de Jager, & Garrard, 2013; Almor, Kempler, MacDonald, Andersen, & Tyler, 1999).…”
mentioning
confidence: 92%